Aquatic Insects Associated with Submerged Macrophytes with Different Morphological Complexities - Douglas F Peiró; Hugo H Saulino; Guilherme Rossi Gorni; Juliano José Corbi; Adrie Pool Vante; Gabriele Amaral (Revista Brasileira Multidisciplinar - ReBraM /Brazilian Multidisciplinay Journal, 2013)
The aim of the study was to analyze the diversity and community structure of aquatic insects associated with species of submersed macrophytes with different morphological complexity in relation to leaf structure. Sampling occurred in raining and dry periods at Ribeirão das Anhumas, Américo Brasiliense/SP. Four macrophytes were analyzed: Vallisneria sp., Eleocharis sp., Egeria najas and Ottelia sp. The entomological community was identified up to the family level, and at tribe level for Chironomidae. The community structure was analyzed using diversity indices of Simpson, Equitability evenness, relative participation of functional category and taxa dominance. The dispersion of faunal composition between the different collection periods was analyzed using a n-MDS with Morisita index. The structure of the insect community associated with macrophytes with different structural morphologies was analyzed using structural similarity calculated by the Bray-Curtis index. Seventeen families were identified from five orders, a total of 1642 specimens. The family Hydropsychidae (Trichoptera) presented eudominance (52.6%), followed by the tribe Pentaneurini (Chironomidae) (13.8%) and family Trichoryithidae (Ephemeroptera) (10%). The results showed that there were no large diversity variations in the analyzed macrophyte species and the sampling periods. The predator and collector functional groups were predominant. The n-MDS analysis indicated the absence of seasonal variation and, the similarity analysis indicated that macrophyte E. najas and Otellia sp., presented similar fauna structure, differing from other analyzed species. The results demonstrated that the morphological structure of macrophytes may have different structures of aquatic insect communities.